Description of larval morphology and phylogenetic relationships of Heterotemna tenuicornis (Silphidae) - Mahlerová, Karolina; Jakubec, Pavel; Novák, Martin; Růžička, Jan (Scientific reports, 2021)
Providing clear and detailed morphological descriptions of endemic species in limited areas enables new knowledge of their biology and ecology to be obtained through citizen science. This information can be further used for their protection. Our study presents the first morphological description of the larvae of all three instars of Heterotemna tenuicornis (Brullé, 1836), an endemic species of the Canary Islands that, together with H. britoi García & Pérez, 1996 and H. figurata (Brullé, 1839), belongs to the peculiar genus Heterotemna Wollaston, 1864. Furthermore, we present the first sequences of two mitochondrial genes (COI, 16S) obtained from larval specimens, and cross reference them with sequences from an adult specimen. Phylogenetic analysis of molecular data placed the genus Heterotemna within the genus Silpha Linnaeus, 1758, suggesting paraphyly of Silpha. In our study, we underline the importance of using a combination of morphological description and molecular data, that can be used for barcoding developmental stages which could not otherwise be definitely associated.
Keywords: brouci; larva; Larva; druhová specificita; zvířata; Coleoptera; Phylogeny; fylogeneze; Bayes Theorem; Bayesova věta; Species Specificity; Animals